Rekonstruksi Konsep Nusyuz Suami Akibat Pergeseran Peran Nafkah dalam Perkara Gugat Cerai di Pengadilan Agama: Perspektif Hukum Islam dan Sosiologi Hukum - Khaerunnisa Zubair; Muhammad Fadil Widhana; Suryadi Syarif; Badaruddin Haba (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The concept of nusyuz in classical fiqh is predominantly addressed only to wives, while a husband’s neglect of maintenance obligations still lacks an equivalent legal term in Indonesian Islamic family law. Religious Court practice shows that most divorce suits filed by wives are grounded in the husband’s failure to provide maintenance, amid the contemporary shift in family economic roles. Using normative legal research with Islamic law and sociology of law approaches, thisarticle examines the limitations of the classical nusyuz concept and reconstructs it, so that the lived reality of many families receives fair legal recognition condition. The findings show that nusyuz is reciprocal in nature and must be reconstructed so that judges possess a fair, responsive and contextual legal framework for family social reality.